Co-infection of Dengue virus by serotypes 3 and 4 in patients from Amazonas, Brazil - Regina M.P. de Figueiredo (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The natural co-infection with dengue virus can occur in highly endemic areas where different serotypes have been observed for many years. We report here four cases of DENV-3/DENV-4 co-infection detected by serological and molecular tests among 674 patients with acute undifferentiated fever from the tropical medicine reference center of Manaus City, Brazil, between 2005 and 2010. Analysis of the sequences obtained indicated the presence of genotype 3 and 1 for DENV-3 and DENV-4 respectively.